Comparison of Efficacy and Safety of Caspofungin Versus Micafungin in Pediatric Allogeneic Stem Cell Transplant Recipients: A Retrospective Analysis. - Maximova, Natalia; Schillani, Giulia; Simeone, Roberto; Maestro, Alessandra; Zanon, Davide (Adv Ther, 2017)
INTRODUCTION: The high morbidity and mortality associated with invasive fungal infections (IFIs) provide the rationale for antifungal prophylaxis in immuno-compromised pediatric patients undergoing hematopoietic stem cell transplantation (HSCT). Caspofungin and micafungin are antifungal agents of interest for prophylaxis of IFIs because of their potency against Candida and minimal toxicity or interactions with other drugs. Few studies have demonstrated the safety and efficacy of such echinocandins as prophylaxis for IFIs in patients undergoing HSCT. METHODS: This retrospective cohort study compared caspofungin and micafungin for prevention of IFIs in 93 pediatric patients undergoing HSCT for oncological or non-oncological disease. The observation began with the first dose of antifungal agent and ended 3 months after transplantation. RESULTS: Patients in the micafungin group had a higher overall treatment success rate of 87.2 versus 84.8% in the caspofungin group, but the difference was not significant. There were no statistically significant differences in the incidence or type of proven/probable IFIs between the 2 groups. The low incidence of death did not differ statistically between the groups. Patients in the caspofungin group presented more frequently with fever, during and after neutropenia. In both groups, we observed an expected worsening of blood chemistry parameters. There were no adverse events definitely attributable to the two antifungal agents. CONCLUSION: These results demonstrate good efficacy and tolerability for caspofungin and micafungin. However, better results with respect to the incidence and resolution of fever in the micafungin group may suggest its use in preference to that of caspofungin.
Keywords: Adolescent; Antifungal Agents; Caspofungin; Child; Child, Preschool; Cohort Studies; Echinocandins; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Infant, Newborn; Lipopeptides; Male; Micafungin; Mycoses; Neutropenia; Retrospective Studies